Practical Training on Automatic Correction of Students’ Answer Sheets Using the EvalBee Application for Teachers at SDN 58 Lubuklinggau: Pelatihan Cara Praktis Koreksi Otomatis Jawaban Siswa Menggunakan Aplikasi Evalbee Pada Guru Di SDN 58 Lubuklinggau - Dea Widaswari; Cahyo Dwi Andita (Room of Civil Society Development, 2026)
Assessment of student learning outcomes in elementary schools is still largely conducted manually, which is time-consuming and increases teachers’ administrative workload. This condition was also found at SDN 58 Lubuklinggau, where teachers had not yet optimally used digital technology to correct students’ answer sheets. This community service program aimed to improve teachers’ knowledge and skills in conducting automatic answer corrections using the EvalBee application based on Optical Mark Recognition (OMR) technology. The program was implemented through socialization, material presentation, hands-on practice, and technical assistance involving 15 teachers. Evaluation was conducted using pretest and posttest questionnaires. The results showed an increase in teachers’ understanding and skills from 45.33% before training to 97.33% after training. Teachers were able to install the application, create answer sheets, scan students’ responses, and download the assessment results. EvalBee was also perceived to accelerate the correction process, improve assessment accuracy, and reduce teachers’ administrative workload. This program shows that practice-based training can serve as a model for strengthening teachers’ digital assessment literacy in elementary schools.